Cognitive Deficit and Aberrant Intrinsic Brain Functional Network in Early-Stage Drug-Naive Parkinson’s Disease - Zhang, Lan; Yang, Tao; Chen, Yuping; Zheng, Denise; Sun, Dong; Tu, Qiang; Huang, Jinbai; Zhang, Junjian; Li, Zezhi (Frontiers in Neuroscience, 2022)
Background: Although cognitive deficit is a common non-motor symptom of Parkinson's disease (PD), the mechanism and valid biomarkers of it have not been identified. To our best knowledge, this was the first study to investigate the intrinsic dysconnectivity pattern of whole-brain functional networks in early-stage drug-naive (ESDN) PD patients and its association with cognitive deficit of PD using voxel-wise Degree Centrality (DC) approach. Methods: A total of 53 ESDN PD patients and 53 healthy controls (HC) were recruited. Resting-state fMRI (rs-fMRI) data were acquired, and voxel-wise DC approach was applied. Electrophysiological testing at P300 amplitude was recorded. The Montreal Cognitive Assessment (MoCA) was conducted to evaluate cognitive performance. Results: ESDN PD patients had lower MoCA scores and P300 amplitudes, but higher P300 latency, than HC (all p<0.0001). PD patients displayed higher DC in the right inferior frontal gyrus (IFG), left medial frontal gyrus (MFG) and left precentral gyrus (PreCG); but lower DC in the left inferior parietal lobule(IPL), left inferior temporal gyrus (ITG), right occipital lobe, and right postcentral gyrus (PoCG) (p Bonferroni correction<0.0001). Interestingly, the DC values of left MFG, right PoCG and right occipital lobe were negatively associated with P300 latency but positively associated with P300 amplitudes and MoCA scores (all p Bonferroni correction<0.0001). Conclusions: Our results indicate the cognitive deficit and abnormal intrinsic brain functional network in ESDN PD patients. The damage of Default Mode Network (DMN) may be contributes to the pathogenesis of cognitive dysfunction in ESDN PD.